PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING UNTUK MENINGKATKAN HASIL BELAJAR ALJABAR SISWA KELAS VIII - Hasanah, Uswatun; Sari, Intan Kemala; Fitra, Rahmat (De Fermat : Jurnal Pendidikan Matematika, 2026)
This research is motivated by the low learning outcomes of students in the material of algebraic operations in class VIII-1 SMP Negeri 1 Sukamakmur. The study aims to determine the improvement of learning outcomes through the application of the Contextual Teaching and Learning (CTL) approach. The method used is quantitative with a pretest–posttest design. The research subjects consisted of 26 students. Data were collected through learning outcome tests in the form of pre-test and post-test, then analyzed using the normality test and the Wilcoxon Signed Rank Test because the data were not normally distributed. The results showed an average pre-test score of 13.80 with a total score of 359 increased to 52.42 in the post-test with a total score of 1,363, with an increase of 38.62 points. The results of the hypothesis test obtained a Z value = -4.458 and a significance of 0.000 <0.05, which indicates a significant increase. Thus, the application of the CTL approach is proven to improve student learning outcomes in the material of algebraic operations.